The Impact of COVID-19 on Provider Perceptions of Telemental Health - Doran, Jennifer M. (Psychiatr Q, 2021)
The present study was designed to assess mental health provider attitudes and perceptions of telemental health (TMH) prior to and during the COVID-19 Pandemic, as well as the nature of their TMH utilization. The study aimed to gather information about positive and negative attitudes towards TMH, perceptions and correlates based on the modality of care, and beliefs about the overall effectiveness of TMH as compared to face-to-face care. The current study is part of a larger mixed methods project utilizing a repeated cross-sectional design. An online survey was administered to a sample of 1448 mental health providers and included demographic and professional information, experiences with and perceptions of TMH prior to and during the COVID-19 Pandemic, as well as a brief measure of pandemic-related stress. The COVID-19 Pandemic resulted in an increased use of TMH in the study sample. During COVID-19, providers reported increased agreement with TMH being necessary, important, and effective for care delivery. Providers who primarily used video, compared with telephone, reported that TMH was more useful, satisfying, and effective. While negative attitude towards TMH was predicted only by prior attitudes and belief in TMH effectiveness, positive attitude towards TMH was also predicted by female sex and current level of pandemic related stress. TMH use during the pandemic was predicted by primary use of video platform and previous TMH use. The 2020 COVID-19 Pandemic resulted in increased use of TMH and significantly increased positive perceptions about TMH among mental health providers. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11126-021-09899-7.